Recurrent Ameloblastic Fibroma: Report of a Rare Case - Ravikumar S. Kulkarni; Amitabh Sarkar; Sandeep Goyal (Hindawi Limited, 2013)
Ameloblastic fibroma (AF) is an uncommon mixed neoplasm of odontogenic origin frequently seen in the second decade of life. It mainly presents as an intrabony lesion but can even occur peripherally. Histologically, our case showed hypercellular areas, an uncommon feature seen in typical AF. Whether this benign lesion is treated by mode of enucleation and curettage or by extensive surgery is still a topic of debate. An extensive surgical treatment is suggested as the initial approach due to its high recurrence rate (18%) and the greater chances of recurrent AFs transforming into ameloblastic fibrosarcoma (45%), together with a long-term followup. We report a case of recurrent AF with hypercellular ectomesenchyme which developed a year after its conservative removal. We conclude that in recurrent AF sufficient sections of the pathological specimen are to be taken to rule out any malignant changes that might have begun in focal areas.